NaCl Nanoparticles as a Cancer Therapeutic. Issue 46 (25th September 2019) - Jiang, Wen; Yin, Lei; Chen, Hongmin; Paschall, Amy Victoria; Zhang, Liuyang; Fu, Wenyan; Zhang, Weizhong; Todd, Trever; Yu, Kevin Shengyang; Zhou, Shiyi; Zhen, Zipeng; Butler, Michael; et al.
Abstract: Many inorganic nanoparticles are prepared and their behaviors in living systems are investigated. Yet, common electrolytes such as NaCl are left out of this campaign. The underlying assumption is that electrolyte nanoparticles will quickly dissolve in water and behave similarly as their constituent salts. Herein, this preconception is challenged. The study shows that NaCl nanoparticles (SCNPs) but not salts are highly toxic to cancer cells. This is because SCNPs enter cells through endocytosis, bypassing cell regulations on ion transport. When dissolved inside cancer cells, SCNPs cause a surge of osmolarity and rapid cell lysis. Interestingly, normal cells are much more resistant to the treatment due to their relatively low sodium levels. Unlike conventional chemotherapeutics, SCNPs cause immunogenic cell death or ICD. In vivo studies show that SCNPs not only kill cancer cells, but also boost an anticancer immunity. The discovery opens up a new perspective on nanoparticle‐based therapeutics. Abstract : NaCl nanoparticles are exploited as a novel type of cancer therapeutic. NaCl nanoparticles are taken up by cancer cells through endocytosis and release large amounts of ions inside them. This causes a drastic increase of osmolarity, leading to cell apoptosis and necrosis. This process is highly immunogenic, stimulating an anti‐cancer immunity that improves local and systemic tumor control.